Maqashid As-AyariÊ»ah sebagai Dasar Pengembangan Ekonomi Islam - Janah, Nasitotul; Ghofur, Abdul (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2018)
In contrast to the secular economy of capitalism and socialism, Islamic Economy is the one built on syariÊ»ah bases, norms and divine transcendent valuesÂ in the divine revelation, the al-QurÊ»an and the á¸¥adiá¹¡. In order to understand the essence of syariÊ»ah, it is necessary to conduct shifting paradigm from a literalist approach merelyÂ focusing on textual and legal meaning to a substantialist approach seeking to capture the moralÂ ideas andÂ Â the original meaning of the syariÊ»ah beyondÂ the text,Â which are trans-historical or transcendental beingÂ and universal (general principle).Â This paradigm shifting occurs asÂ the text is limited while the reality is infinite. Among the substantialistÂ approaches offered isÂ the use of maqashid syariÊ»ah and mashlaá¸¥ah.Â Maqashid syariÊ»ah refers to the essence of God's intention (Law Giver), which is the most essential formulated into five elements, they are: ØÙØ¸ Ø§Ù„Ø¯ÙŠÙ† Â (the religion keeping), ØÙØ¸ Ø§Ù„Ù†ÙØ³ Â (the soul keeping), ØÙØ¸ Ø§Ù„Ø¹Ù‚Ù„ Â (the intellect keeping), ØÙØ¸ Ø§Ù„Ù†Ø³Ù„ (descendant keeping) and Ø§Ù„Ù…Ø§Ù„ ØÙØ¸ (the wealth keeping). Then, hierarchically, maqashid in classical theory is developed into 3 levels: Ø§Ù„Ø¶Ø±ÙˆØ±ÙŠØ© Â (primary needs /basicÂ necessity), Ø§Ù„ØØ§Ø¬ÙŠØ© Â (secondary needs), and Ø§Ù„ØªØØ³ÙŠÙ†ÙŠØ© Â (tertiary needs). Under the argument of maqashid syariÊ»ah,Â this Islamic economic concept must be developed, thereforeÂ on the one hand the Islamic economy will not lose its divine morality, but on the other hand it can also develop dynamically, progressively and even ready to handle theÂ contemporary economic problems. Based on the explanation above, this research is focused on what is the basic philosophy that is the basis of the formulation and development of Islamic economics? This research data is library. The data collection method uses the documentation method, namely: collecting, then reviewing the data collected. After the data is collected, the data is analyzed by reducing data, presenting data in narrative form, and drawing conclusions. This study concludes that the Islamic Economy is closely related to the maqashid syariÊ»ah namely á¸¥ifáº“ al-mal. Maqashid syariÊ»ah is the basis for the development of the Islamic economy because it aims at the goal of creating human welfare and happiness by balancing the circulation of property fairly and balanced both personally and socially. Understanding of maqashid syariÊ»ah is a necessity in berijtihad to answer various economic problems. Understanding of maqashid syariÊ»ah is not only needed to formulate macroeconomic policies, but also policies that are microeconomic. In the economic context, maqashid syariÊ»ah has a dual role, namely: as a means of control as well as a social engineering tool to realize human equality. He provides a rational philosophical basis of economic activity. Without the maqashid syariÊ»ah, the understanding and practice of Islamic economics will be narrow, rigid, static, and slow. Islamic economics will lose the spirit and substance of its shari'a. But on the contrary, with the maqashid syariÊ»ah the Islamic economy develops elastic, dynamic, in accordance with the character of the ShariÊ»ah Islam which is universal and relevant for all space and time